2016
DOI: 10.17269/cjph.107.5231
|View full text |Cite
|
Sign up to set email alerts
|

Implicating municipalities in addressing household food insecurity in Canada: A pan-Canadian analysis of news print media coverage

Abstract: OBJECTIVES: Household food insecurity (HFI) affects approximately 13% of Canadian households and is especially prevalent among low-income households. Actions to address HFI have been occurring primarily at the local level, despite calls for greater income supports from senior governments to reduce poverty. News media may be reinforcing this trend, by emphasizing food-based solutions to HFI and the municipal level as the site where action needs to take place. The objective of this study was to examine the level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
0
6
0
1
Order By: Relevance
“…The Trussell Trust is a UK-based NGO that supports a network of food banks while working and campaigning to end the need for food banks. Another study found a negative tone was adopted when senior governments were implicated in actions to address food insecurity, compared to more neutral and positive tones when local/municipal governments were profiled ( Collins et al ., 2016 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The Trussell Trust is a UK-based NGO that supports a network of food banks while working and campaigning to end the need for food banks. Another study found a negative tone was adopted when senior governments were implicated in actions to address food insecurity, compared to more neutral and positive tones when local/municipal governments were profiled ( Collins et al ., 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…Across most studies ( n = 7), newspaper reporting on charitable food aid was predominately positive ( Wells and Caraher, 2014 ; Collins et al ., 2016 ; Knight et al ., 2018 ; Tikka, 2019 ; Price et al ., 2020 ; Smith-Carrier, 2021 ; Yau et al ., 2021 ). When food banks were framed as distributors of food waste it was considered a double win for both the environment and food poverty ( Tikka, 2019 ; Yau et al ., 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…No se presenta ninguna crítica o cuestionamiento Industrial Cuestionamiento a los sistemas basados en compra de alimentos e ingresos económicos como alternativas: huertos comunitarios/agricultura urbana fueron los más comúnmente descritos, seguidos de los bancos de alimentos/programas de comidas, para combatir inseguridad alimentaria (Collins et al, 2016).…”
Section: Híbrido O Mixtounclassified